INTRODUKSI PENGOLAHAN SELE KACANG TANAH SEBAGI PANGAN KAYA NUTRISI DAN ENERGI DI DESA NEGARI KLUNGKUNG - AGUS SELAMET DUNIAJI; WISANIYASA WISANIYASA (Buletin Udayana Mengabdi, 2008)
ABSTRACT Almost all of the production of peanut in Indonesia is locally consumed. The peanuts are consumed in various ways, mostly through direct consumption such as boiled peanut, fried peanut, roasted peanut, peanut convectors and peanut butter.Peanut Butter is by far the most important product made from peanuts. It is the pasta forming food that is usually consumed with bread. Peanut Butter is the most popular as a high and medium class food and almost found it at the restaurant and supermarket in Indonesia. However, to process peanut butter is not so difficult for everybody who wants to do it. Peanut Butter processing is very simple with the equipment and ways properly such as to prepare good quality peanuts, sorted, drying, testa separated, grounding and boiling with mixing sugar and salt. Peanut butter has a high calorie with a good nutrition such as protein, fat, vitamins and trace element like calcium, zinc and magnesium. Reformulation and process improvement of Peanut Butter had been done at Department of agricultural products technology, Udayana University and had been disseminated to the housewife’s group and farmer’s group in Negari Village. Through the technology transfer of the Peanut Butter processing, we hope will be achieved a good quality and many several of peanuts processing in the future.